Relevansi Pembelajaran Berbasis Buku Teks IPS dalam Konteks Implementasi Kurikulum Merdeka di SMP 236 Jakarta - Ayudhia Nur Luthfia; Sujarwo S (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to evaluate the level of relevance of social studies textbook-based learning to the implementation of Merdeka Curriculum in SMP 236 Jakarta, by considering the views of teachers and students. This research method uses a mixed approach, combining quantitative analysis of survey data and qualitative analysis through in-depth interviews with teachers and students. The results of the analysis show that there are a number of aspects of social studies textbooks that are considered relevant to the objectives and context of Merdeka Curriculum, but there are also elements that need to be updated or adjusted. The views of teachers and students provide valuable insights into the effectiveness and need for improvement in the implementation of social studies textbooks in the context of the new curriculum. The implications of these findings make a significant contribution to the development of a more adaptive and needs-oriented curriculum for students at SMP 236 Jakarta and schools in similar contexts.